Relationships between atmospheric organic compounds and air-mass exposure to marine biology - Arnold, S. R.; Spracklen, D. V.; Gebhardt, S.; Custer, T.; Williams, J.; Peeken, Ilka; Alvain, S. (Environmental Chemistry, 2010)
Environmental context. The exchange of gases between the atmosphere and oceans impacts Earth’s climate. Over the remote oceans, marine emissions of organic species may have significant impacts on cloud properties and the atmosphere’s oxidative capacity. Quantifying these emissions and their dependence on ocean biology over the global oceans is a major challenge. Here we present a new method which relates atmospheric abundance of several organic chemicals over the South Atlantic Ocean to the exposure of air to ocean biology over several days before its sampling. Abstract. We have used a Lagrangian transport model and satellite observations of oceanic chlorophyll-a concentrations and phytoplankton community structure, to investigate relationships between air mass biological exposure and atmospheric concentrations of organic compounds over the remote South Atlantic Ocean in January and February 2007. Accounting for spatial and temporal exposure of air masses to chlorophyll from biologically active ocean regions upwind of the observation location produces significant correlations with atmospheric organohalogens, despite insignificant or smaller correlations using commonly applied in-situ chlorophyll. Strongest correlations (r = 0.42–0.53) are obtained with chlorophyll exposure over a 2-day transport history for CHBr3, CH2Br2, CH3I, and dimethylsulfide, and are strengthened further with exposure to specific phytoplankton types. Incorporating daylight and wind-speed terms into the chlorophyll exposure results in reduced correlations. The method demonstrates that conclusions drawn regarding oceanic trace-gas sources from in-situ chlorophyll or satellite chlorophyll averages over arbitrary areas may prove erroneous without accounting for the transport history of air sampled.